International Financial Reporting Standards Adoption and Liquidity Performance of Food and Beverages Listed Companies: Empirical Evidence from Nigeria - Junaidu, Abubakar Sambo; Ahmadu, Haruna (Growth, 2019)
Despite the relevance and adaptations of International Financial Reporting Standard (IFRS) in Nigeria, the literature indicates very few studies have attempted to investigate the effect of IFRS adoption to the firm’s performance, specifically, the relationship between IFRS adoption and liquidity performance of food and beverages listed companies in Nigeria. The literature suggests that there is not only limited information on the impact of IFRS adoption but also little research in this important area of study. Based on this information and research gab, the objective for the study is to investigate the effect of IFRS adoption on liquidity performance of food and beverages listed companies in Nigeria. By using Secondary data was collected from the annual reports of the sample companies. Multiple ordinary least square (OLS) regression was used to analyse the data collected from the audited financial statements of the sampled companies. I-T test and J-T test were also applied to test for any significant increase in firm performance after the adoption of IFRS. The analysed result showed that there is significant relationship between IFRS adoption and liquidity performance of food and beverages companies listed in the NSE. The implication of this study is that, the practice of the adoption of IFRS should be given more emphasis by organisations in Nigeria. The finding of the study indicates that, organisations that adopt IFRS would be able to improve their liquidity performance.